Coicis Semen for the treatment of malignant tumors of the female reproductive system: A review of traditional Chinese medicinal uses, phytochemistry, pharmacokinetics, and pharmacodynamics - Pan, Xue; Shen, Qian; Zhang, Chuanlong; Zhang, Xiyuan; Li, Yi; Chang, Zhuo; Pang, Bo (Frontiers in Pharmacology, 2023)
Coicis Semen is an important food product and traditional Chinese medicine (TCM) derived from the dried and mature seeds of Coix lacryma-jobi L.var.ma-yuen (Roman.) Stapf. An increasing number of studies have investigated its use, either alone or in combination with other botanical drugs, to treat female reproductive system malignancies, and its pharmacological effects have been confirmed clinically. This review aims to provide an overview of Coicis Semen’s historical role in treating female reproductive system malignancies based on TCM theory, to summarize clinical trials results, and to analyze information pertaining to the main phytochemical components, pharmacokinetics, related anti-cancer pharmacological effects, and toxicology of Coicis Semen. Information on Coicis Semen was collected from internationally accepted scientific databases. Seventy-four clinical trials were identified that used Coicis Semen in combination with other Chinese medicine to treat female reproductive system malignancies, most of which demonstrated good anti-tumor efficacy and few adverse reactions. To date, more than 80 individual compounds have been isolated from this botanical drug. In terms of anti-tumor effects, Coix seed oil has been studied the most. Pharmacokinetic data suggest that the active ingredients in Coicis Semen are widely distributed after administration, and Coicis Semen and its active compounds play a beneficial role in treating female reproductive system malignancies. Mechanistically, the anti-cancer effects may be related to inhibition of tumor cell proliferation and promotion of apoptosis, inhibition of tumor angiogenesis, suppression of the chronic inflammatory microenvironment of tumors, modulation of immune function, and regulation of the female reproductive system. Most acute toxicity and genotoxicity studies have shown that Coicis Semen is nontoxic. However, the existing studies have many limitations, and the future research direction should emphasize 1) the relationship between drug concentration and pharmacological action as well as toxicity; 2) the structural modification or the synthesis of analogues led by the active ingredients of Coicis Semen to enhance pharmacological activities and bioavailability; 3) accurately revealing the anti-cancer pharmacological effects of Coicis Semen and its compounds through multi-omics technology. We hope that this review can determine future directions and inform novel drug development for treating female reproductive malignancies.